Determining Purpose through Metafunctional Meanings: A Discourse Analysis of Two Speeches in Acts 2 and 17 - Jung, Jae Cheon (My University, 2023)
There are a large number of character speeches in Acts. Scholars have used various means and methods to contribute to a feasible and plausible answer regarding the functions of speeches in Acts. Unfortunately, the studies have often been focused on the authenticity of the speeches: were they Luke's creation or simply his compilation? This dissertation presents another set of tools for scholars to revisit Luke's speeches in Acts in order to add insight into their questions, and also to broaden the realm of this narrow focus. In particular, I will implement and demonstrate how to use modern linguistics, namely discourse analysis based on Halliday's Systemic Functional Linguistics. The present study ventures to apply this linguistic insight by focusing on two speeches in the Acts of the Apostles, Acts 2:14-36 and 17:22-31. If scholars wish to study the speeches of Acts further, or any New Testament speeches, hopefully this dissertation will provide a helpful approach to meet their needs. Thus, analyzing and comparing the author's functionally linguistic choices in these two speeches with regards to similarities and differences will describe his specific use of these speeches. The most notable contribution of the dissertation will be found in implementing a new approach to the study of speeches in Acts. I also hope such a due recognition of the language will motivate and inspire further linguistic explorations into various areas, which remain perplexed by other approaches.
Keywords: Purpose, Metafunctional Meanings, Metafunction, Discourse, Discourse Analysis, Speeches, Acts 2, Acts 17, Acts, The Book of Acts, Character Speeches, Luke, Gospel Writer, Linguistics, Modern Linguistics, Halliday, SFL, Systemic Functional Linguistics, The Acts of the Apostles, Acts 2:14-36, Acts 17:22-31